Clinical Application of Near-Infrared Thoracoscopy With Indocyanine Green in Video-Assisted Thoracoscopic Anatomical Segmentectomy. (August 2019) - Jin, Yuxiang; Wang, Mingdong; Xue, Lei; Zhao, Xuewei
Background. To confirm the impact of near-infrared thoracoscopy with intravenous injection of indocyanine green (ICG) during video-assisted thoracic surgery (VATS)-based segmentectomy. Materials and Methods . We retrospectively screened the perioperative data in total 21 patients who underwent segmentectomy by VATS. The segmental arteries and bronchi were identified with the help of preoperative 3-dimensional computed tomography images. Among them, clinical effectiveness and postoperative complications were analyzed. VATS segmentectomy was performed using a 3-port approach with systemic intravenous injection of ICG. Results. A total of 21 patients underwent VATS-based segmentectomy with ICG injection. The mean operation time was 126.19 ± 15.32 minutes, and the mean bleeding volume was 158.10 ± 39.95 mL. In addition, the average drainage volume 1 day after surgery was 153.81 ± 32.19 mL, and mean duration of drainage was 1.62 ± 0.59 days. Complications occurred in 6 of the 21 patients. Two patients had pneumonia, 3 had arrhythmia, and 1 had prolonged air leak. There were no complications resulting from ICG angiography. Conclusions. Near-infrared thoracoscopy with intravenous injection of ICG is a safe, fast, simple, and highly accurate method that can be used to identify the intersegmental plane and facilitate the quality of VATS-based segmentectomy.